2014
DOI: 10.1007/s00204-014-1356-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in carbon nanotube-generated health effects

Abstract: The development of products containing carbon nanotubes (CNTs) is a major achievement of nanotechnology, although concerns regarding risk of toxic effects linger if the hazards associated with these materials are not thoroughly investigated. Exposure to CNTs has been associated with depletion of antioxidants, increased intracellular production of reactive oxygen species and pro-inflammatory signaling in cultured cells with primary function in the immune system as well as epithelial, endothelial and stromal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
52
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 211 publications
0
52
0
3
Order By: Relevance
“…Rigid needle-like ENM can also cause phagocyte death by literally perforating the cell membrane (102).…”
Section: Pre-peer-review Manuscriptmentioning
confidence: 99%
“…Rigid needle-like ENM can also cause phagocyte death by literally perforating the cell membrane (102).…”
Section: Pre-peer-review Manuscriptmentioning
confidence: 99%
“…69,70 Exposure to CNT resulted in adverse effects in various cell types in vitro, including those with immune-related functions, such as macrophages (mφ) (rat alveolar mφ [NR8383] and THP1-derived mφ), human microvascular endothelial cells, human epidermal keratinocytes, human bronchial epithelial (BEAS-2B), human mesothelial (MeT-5A) cells, and lymphoblastoid (MCL-5) cells. 71 In vivo studies have shown depletion of antioxidants, increased intracellular production of ROS, and proinflammatory signaling, resulting in fibrosis and neoplastic changes in the lungs of mice and rats and elevated risk of cardiopulmonary diseases by generation of a proinflammatory and prooxidant milieu in the lungs. 71 For nanosilver, immunosuppression was observed after 28-day repeated dose intravenous administration to Wistar rats, 72,73 although no immunotoxicity was observed in another study using oral administration.…”
mentioning
confidence: 99%
“…71 In vivo studies have shown depletion of antioxidants, increased intracellular production of ROS, and proinflammatory signaling, resulting in fibrosis and neoplastic changes in the lungs of mice and rats and elevated risk of cardiopulmonary diseases by generation of a proinflammatory and prooxidant milieu in the lungs. 71 For nanosilver, immunosuppression was observed after 28-day repeated dose intravenous administration to Wistar rats, 72,73 although no immunotoxicity was observed in another study using oral administration. 74 Some NMs can interact with the immune system in a direct way through toll-like receptors (TLRs).…”
mentioning
confidence: 99%
“…In particular, research on oxidative stress induced by nanosized materials has become more and more important in recent years (Møller et al 2014;Zhang et al 2015;Bondarenko et al 2013). Moreover, the relatively high exposure of humans to some heavy metals (Hengstler et al 2003;King et al 2015;Jaishankar et al 2014;Tom and Fletcher 2014;Shiue and Hristova 2014;Pizzino et al 2014;Jung et al 2003) has motivated intensive research on metal toxicity, including nickel-induced DNA damage (Yao and Costa 2014), manganese-induced neurotoxicity (Krishna et al 2014;Kumasaka et al 2014), and lead-associated mimicry of essential minerals and immunotoxicity (Breton et al 2013;Jorissen et al 2013).…”
mentioning
confidence: 99%